Oficina | EPS LORETO S.A - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1999)
SPANISH: EPS LORETO S.A. Sedaloreto es una Entidad Prestadora de Servicios de Saneamiento de agua potable y alcantarillado en Loreto, ubicando su oficina en la calle Huallaga, Iquitos y su planta de agua residuales en la Av. guardia civil 1260- pampachicaubicado
ENGLISH: EPS LORETO S.A. Sedaloreto is an entity that provides potable water and sewage sanitation services in Loreto. Its office is located on Huallaga Street, Iquitos and its wastewater plant is located at Av. guardia civil 1260- pampachica, in the city of Iquitos.

SPANISH: EPS LORETO S.A. Sedaloreto es una Entidad Prestadora de Servicios de Saneamiento de agua potable y alcantarillado en Loreto, ubicando su oficina en la calle Huallaga, Iquitos y su planta de agua residuales en la Av. guardia civil 1260- pampachicaubicado
ENGLISH: EPS LORETO S.A. Sedaloreto is an entity that provides potable water and sewage sanitation services in Loreto. Its office is located on Huallaga Street, Iquitos and its wastewater plant is located at Av. guardia civil 1260- pampachica, in the city of Iquitos.
Office
Keywords: Iquitos (Perú)|~|Service--Water --Organization|~|Servicio|~|Agua|~|Entidad|~|Iquitos (Perú)